ALGUNAS CONSIDERACIONES SOBRE EL SARCÓFAGO CON MUSAS Y PENSADORES DEL MUSEO DE LA CATEDRAL DE MURCIA - Noguera Celdrán, José Miguel (Imafronte, 1993)
This paper analyzes little studied features of a Roman sarcophagus, the front of which is now preserved at the Cathedral of Murcia Diocese Museum. From left to right, its side by side turgid relief shows the figures of Polymnia, Calliope, Urania, Terpsichore, Thalia, the dead woman, Euterpe, Melpomene and Clio. The spaces between each pair of figures are covered with evocations of five philosophers (among the Homer and Socrates). Though some authors have posed interpretations of the figure that we presume to be the deceased, it is not probable that it is symbolically assimilated to Erato (the only of the Nine Sisters not shown in the relief ); we better consider the representation among Muses-patrons of the fields of Art and Knowledge, and wise men, who cultivated Science and Humanities as a way to show the educated mood of the deceased and her belief that un everlasting life beyond death can be gained through intellectual tasks.